The closed and compact domain organization of the 70-kDa human cytochrome P450 reductase in its oxidized state as revealed by NMR. - Vincent, B; Morellet, N; Fatemi, F; Aigrain, L; Truan, G; Guittet, E; Lescop, E (2012)
The NADPH cytochrome P450 reductase (CPR), a diflavin enzyme, catalyzes the electron transfer (ET) from NADPH to the substrate P450. The crystal structures of mammalian and yeast CPRs show a compact organization for the two domains containing FMN (flavin mononucleotide) and FAD (flavin adenine dinucleotide), with a short interflavin distance consistent with fast ET from the NADPH-reduced FAD to the second flavin FMN. This conformation, referred as "closed", contrasts with the alternative opened or extended domain arrangements recently described for partially reduced or mutant CPR. Internal domain flexibility in this enzyme is indeed necessary to account for the apparently conflicting requirements of having FMN flavin accessible to both the FAD and the substrate P450 at the same interface. However, how interdomain dynamics influence internal and external ETs in CPR is still largely unknown. Here, we used NMR techniques to explore the global, domain-specific and residue-specific structural and dynamic properties of the nucleotide-free human CPR in solution in its oxidized state. Based on the backbone resonance assignment of this 70-kDa protein, we collected residue-specific (15)N relaxation and (1)H-(15)N residual dipolar couplings. Surprisingly and in contrast with previous studies, the analysis of these NMR data revealed that the CPR exists in a unique and predominant conformation that highly resembles the closed conformation observed in the crystalline state. Based on our findings and the previous observations of conformational equilibria of the CPR in partially reduced states, we propose that the large-scale conformational transitions of the CPR during the catalytic cycle are tightly controlled to ensure optimal electron delivery.